ANALYSIS OF THE RICE SUPPLY CHAIN IN TANAH LAUT REGENCY TO SUPPORT FOOD SECURITY - Elivi Sofi Salafiah,; Azelia Puteri1,; Barokah, (Journal of Smart Agribusiness and Digitalization, 2026)
This study analyzes the rice supply chain in Tanah Laut Regency, South Kalimantan, to support regional food security. While extensive agricultural supply chain research focuses on major production hubs in Java, empirical evidence from outer-island regional frameworks remains critically understudied. This research employs a qualitative descriptive approach to map and evaluate the multidirectional flows of products, finances, and information. Data collection was conducted from September to October 2025 across several key rice-producing areas within the regency. Utilizing a snowball sampling technique, 20 key stakeholders were interviewed, including rice farmers, collectors, large-scale agents, and traditional retailers. Source triangulation and cross-validation among entities were utilized to ensure empirical data validity and methodological rigor. The findings indicate that the regional rice supply chain is predominantly conventional, fragmented, and lacks full integration, operating through three distinct distribution channels dominated by intermediary collectors. The mapping of the bidirectional flows uncovers critical operational bottlenecks, specifically high logistical risks of post-harvest quality degradation, severe price information asymmetry, and an uneven distribution of profit margins that disadvantages smallholder farmers. Consequently, the overall efficiency of the distribution network remains low, creating localized price fluctuations and supply vulnerabilities that threaten regional food security. To mitigate these systemic inefficiencies, this study recommends targeted strategic interventions, including the institutional strengthening of farmer cooperatives to improve collective bargaining power, the deployment of transparent digital information platforms to eliminate price manipulation, and public capital investments in localized post-harvest facilities.